Exon shuffling and alternative splicing of ROCO genes in brown algae enables a diverse repertoire of candidate immune receptors - Teng, Linhong; Sun, Yuhuan; Chen, Jiayi; Wang, Chenghui; Urbach, Jonathan M.; Kobe, Bostjan; Ye, Naihao; Zeng, Qiangcheng (Frontiers in Plant Science, 2024)
The ROCO family is a family of GTPases characterized by a central ROC-COR tandem domain.Interest in the structure and function of ROCO proteins has increased with the identification of their important roles in human disease. Nevertheless, the functions of most ROCO proteins are still unknown. In the present study, we characterized the structure, evolution, and expression of ROCOs in four species of brown algae. Brown algae have a larger number of ROCO proteins than other organisms reported to date. Phylogenetic analyses showed that ROCOs have an ancient origin, likely originated in prokaryotes. ROCOs in brown algae clustered into four groups and showed no strong relationship with red algae or green algae. Brown algal ROCOs retain the ancestral LRR-ROC-COR domain arrangement, which is found in prokaryotes, plants and some basal metazoans. Remarkably, individual LRR motifs in ROCO genes are each encoded by separate exons and exhibit intense exon shuffling and diversifying selection. Furthermore, the tandem LRR exons exhibit alternative splicing to generate multiple transcripts. Both exon shuffling and alternative splicing of LRR repeats may be important mechanisms for generating diverse ligand-binding specificities as immune receptors. Besides their potential immune role, expression analysis shows that many ROCO genes are responsive to other stress conditions, suggesting they could participate in multiple signal pathways, not limited to the immune response. Our results substantially enhance our understanding of the structure and function of this mysterious gene family.